Chemical Dermal Exposure Risk Assessment in the Water Treatment Plant of Fertilizer Industry - Rahmawati, Rizki; Tejamaya, Mila (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction:In water treatment plants (WTP), chemicals play a crucial role. However, some of these chemicals are hazardous. This study aims to conduct a dermal risk assessment in the WTP of an ammonia and urea production facility. Methods: The study was performed in August 2023 and assessed dermal exposure risk for four hazardous chemicals: NaOCl (30%), HCl (60%), H2SO4 (98%), and NaOH (48%), utilizing the Tier 2 RISKOFDERM model. Intrinsic toxicity was evaluated using risk phrases and toxicity information. Potential dermal exposure rates (PERBODY and PERHANDS) were determined based on task group and exposure modifier, while actual dermal exposure rates (AERBODY and AERHANDS) were determined based on clothing type and activity time. Health risk was assessed using actual exposure scores and intrinsic toxicity levels, which were categorized into 10 different levels ranging from 1 to 10. Results: The risk phrases indicated that four chemicals possessed a high level of intrinsic toxicity in terms of local effect but no systemic effect. PERBODY and PERHANDS were high (NaOCl, HCl) and low (H2SO4, NaOH). The actual exposure scores were determined to be 1 (high) for NaOCl and HCI, 0.01 (low) for H2SO4, and 0.03 (medium) for NaOH. Health risk values were 8 for NaOCl and HCI, 5 for H2SO4, and 6 for NaOH. Conclusion: Health risks in NaOCl and HCl were assigned action priority (AP) 1, followed by NaOH at AP-2, and H2SO4 at AP-3. The study recommends the implementation of control measures encompassing engineering solutions, administration, and personal protective equipment.